Perjalanan Digitalilasi Aksara Bali: Dari Lontar ke Layar dalam Konteks Pelestarian dan Modernisasi Budaya (Studi Tahun 2010-2015) - Budiasti, Ni Wayan (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
As one of the rich cultural heritages, the Balinese script plays a vital role in maintaining traditional Balinese values. The lontar manuscript used as a writing medium has become integral to Balinese history. However, with the entry of modernization, the existence of lontar is increasingly threatened by physical damage and the loss of a generation that can read and write Balinese script. The digitization of the Balinese script is an important solution for preserving this culture. This article examines the journey of digitization of Balinese script from lontar to screen in the context of cultural preservation and modernization from 2010-2015. The research method used is a comprehensive literature review, which analyzes various literature and previous research related to the digitization of the Balinese script and the preservation of the lontar script. The study results show that digitalization provides easy access to lontar scripts, expands the range of Balinese script learning, and introduces Balinese culture to the international world. Although digitization offers many benefits, there are still challenges related to the accuracy of recognizing Balinese script in digital format, especially in degraded manuscripts. This research contributes to developing digital technology that is more adaptive to the Balinese script and provides solutions for preserving Balinese culture in the digital era. In conclusion, digitization of the Balinese script is not only a technical conservation measure but also a means to maintain its relevance amid the current growing modernization.